Neutralization Techniques: the Role of Narratives in Criminal Thinking - Guerra Castañeda, Andrés Tarsicio (Ius Humani. Jornal do direito, 2025)
This paper presents an epistemological proposal aimed at grounding the criminological theory known as techniques of neutralization from an interdisciplinary perspective. To this end, it draws on theories from law, criminology, philosophy, and particularly cultural psychology. The goal is to explain how narratives operate in the activation and justification of crime.